Functional yogurt fermented by two‐probiotics regulates blood lipid and weight in a high‐fat diet mouse model. Issue 9 (31st May 2022) - Cai, Qinling; Song, Yahui; Wang, Shanglong; Wang, Weihong; Sun, Xiaopeng; Yu, Jia; Wei, Yuxi
Abstract: We investigated the blood lipid regulation effects and mechanism of a functional Natto yogurt in a high‐fat diet‐induced hyperlipidemia mouse model. Natto yogurt was characteristically fermented by Bacillus natto and Lactobacillus plantarum with milk‐soy dual protein as substrates. After 5 weeks of Natto yogurt consumption, the body weight, fat, and liver weight of mice were significantly improved, while serum levels of TG, TC, LDL, ALT, TBIL, and TBA were reduced. Natto yogurt significantly decreased the area of liver fat infiltration and the number of lipid droplets. In mechanism, we found that Natto yogurt can inhibit fatty acid synthesis and enhance fatty acid catabolism by regulating the expression of PPARα, PPARγ, CD36 and FAS in the liver. Moreover, Natto yogurt increased the ratio of Bacteroidetes to Firmicutes in the intestine. These results provide a possibility for Natto yogurt as a dual protein functional food to prevent and treat hyperlipidemia and obesity. Practical applications: Traditional‐fermented yogurt promotes nutritional absorption and reduces blood pressure and fat, while Bacillus natto and its fermented food have been proved to play a significant role in improving cardiovascular and cerebrovascular diseases and obesity. Therefore, we developed a new dual protein functional yogurt (Natto yogurt) fermented by B. natto and Lactobacillus plantarum with milk and soy as substrates. We found that Natto yogurt could notably regulate blood lipid by inhibiting the synthesis of fatty acids, accelerating the catabolism of fatty acids, reducing liver damage, and increasing the abundance of beneficial intestinal microorganisms. This study suggested that Natto yogurt could improve hyperlipidemia and obesity as a safe, effective, and healthy functional food. Abstract : We developed a new dual protein functional yogurt fermented by Bacillus natto and Lactobacillus plantarum with milk and soy as substrates. Our results demonstrated that Natto yogurt could improve blood lipid by inhibiting the de novo synthesis of fatty acids, accelerating the catabolism of fatty acids, reducing liver damage, and increasing the richness of beneficial intestinal microorganisms. Therefore, it is possible that Natto yogurt could prevent and treat hyperlipidemia and obesity as a functional food.